IMPLEMENTASI PENANGANAN KASUS KEKERASAN TERHADAP ANAK OLEH KOMISI PERLINDUNGAN ANAK INDONESIA - Melati, Dwi Putri (FIAT JUSTISIA, 2015)
The Government held protection of children with a Child Protection Commission based on the mandate Presidential Decree Number 77 of 2003 on Child Protection Commission and Law Number 23 of 2002 on Child Protection. The problem of Indonesian Child Protection Commission (KPAI) implementation in handling cases of violence against children and Protection Commission apasaja resistance factors Indonesian Children to the protection cases of violence against children. Writing nomative juridical approach and use nomative juridical approach empirical. Discussions on Normative KPAI socialization gather data and information, received complaints review, do, monitoring, and evaluation, report, advice inputs, and consideration to the President. KPAI will ideally plays a monitor, monitor and encouragement organizer child protection, policy advocacy, as the mediator in the handling cases of violence against children. Some of the factors that would be resistance KPAI in dealing with cases of violence against children in terms of the method seen from law enforcement officials, the law,the lack public understanding on childrens rights, facilities as the minimum support infrastructure, there is a tradition negative community authors suggest that Indonesian Child Protection Commission raises really carry out an effective and professional, the Government gives infrastructure, facilities, facilities and infrastructure that enough, people can understand childrens rights and understand.Keywords : Implementation, Handling, Children.